Effect of diode laser on antioxidant enzymes of salivary glands in diabetic rats. Issue 1 (January 2017) - El-Sadek, Hoda; El-Hadidi, Sahar M.A.; Aboul-Ezz, Eman H.A.; Fateen, Ekram M.; Sobhy, Amr G.; Rashed, Laila A.; Yehia, Hussein
Abstract : Introduction: Diabetes mellitus is a heterogenous clinical disorder, a genetically complex disease, with both genetic and environmental factors contributing to its development. It constitutes a major public health problem. Elevated blood glucose level is a characteristic finding in afflicted patients. Hyperglycemia increases the activity of antioxidant enzymes such as catalase and peroxidase enzymes consequent to increased reactive oxygen species. Trials of low-level laser therapy (LLLT) on humans found improvement in xerostomia associated with the disorder. The aim of this study was to investigate the effect of laser irradiation on the enzymatic activities of catalase and glutathione peroxidase in the salivary glands of diabetic rats. Materials and methods: The study included 60 healthy adult female rats. They were divided into four groups: normal (group I), untreated diabetic group (group II), and treated diabetic groups (III and IV). Their parotid and submandibular glands were subjected to LLLT (5 and 20 J/cm 2, respectively). Biochemical analysis was performed to detect catalase and glutathione activities in these glands using a spectrophotometer. Results: The specific activities of catalase and glutathione peroxidase enzymes were significantly increased in group II compared with group I. The catalase activity of the irradiated parotid salivary gland was significantly reduced in groups III and IV, whereas nonsignificant reduction in glutathione activity was noticed in the parotid salivary gland of the irradiated group. A significant decrease in catalase enzyme activities was seen on the submandibular salivary gland in groups III and IV. Glutathione peroxidase activity showed a significant decrease in activity only in group III in the submandibular salivary gland. Blood glucose level was significantly decreased following laser irradiation in group III but not in group IV. Conclusion: LLLT might be an adjunct to treatment for salivary gland complications in diabetic patients.